Ultrasonic irradiation-promoted one-pot synthesis of CH3NH3PbBr3 quantum dots without using flammable CH3NH2 precursor. (27th February 2017) - Jiang, Han; Wang, Chunlei; Lv, Changgui; Xu, Shuhong; Zhu, Li; Zhang, Ruohu; Cui, Yiping
Abstract: At present, the CH3 NH3 PbBr3 quantum dots (QDs) reported in the literature usually contain two synthesis steps: the initial preparation of CH3 NH3 Br via the reaction of flammable CH3 NH2 and HBr, together with the subsequent formation of CH3 NH3 PbBr3 QDs. To avoid the use of dangerous CH3 NH2, this work develops a novel one-pot method for synthesizing CH3 NH3 PbBr3 QDs using safe and commercially available reactants (CH3 NH3 Cl, KBr and PbCl2 ). It is found that ultrasonic treatment plays a key role during the synthesis of CH3 NH3 PbBr3 QDs. Without ultrasonic irradiation, it is not possible to synthesize CH3 NH3 PbBr3 QDs under heating or vigorous stirring. Aliquots of samples taken at different ultrasonic irradiation time intervals show a time-dependent redshift in the emission wavelength. This suggests the formation of CH3 NH3 PbCl3 QDs first, followed by the formation of CH3 NH3 PbBr3 QDs through ultrasonically promoted halide exchange. Moreover, mixed CH3 NH3 PbCl x Br3− x QDs with a tunable emission wavelength can also be prepared through this one-pot method by controlling the ultrasonic irradiation time. In comparison to the previous two-step method, the current one-pot method is simpler, less time-consuming and does not use flammable CH3 NH2 . The as-prepared CH3 NH3 PbBr3 QDs show a comparable photoluminescence (PL) quantum yield (QY) to that of the literature. What is more, the ultrasonic time-controlled emission wavelength of CH3 NH3 PbCl x Br3− x QDs also provides an alternative way of tuning QD emission to the traditional way of controlling the halide ratios.